Review: Fluid biomarkers for frontotemporal dementias. (3rd December 2018) - Zetterberg, H.; van Swieten, J. C.; Boxer, A. L.; Rohrer, J. D.
Abstract : Frontotemporal dementias (FTDs) are clinically, genetically and pathologically heterogeneous neurodegenerative disorders that affect the frontal and anterior temporal lobes of the brain. They are relatively common causes of young‐onset dementia and usually present with behavioural disturbance (behavioural variant FTD) or language impairment (primary progressive aphasia), but there is also overlap with motor neurone disease and the atypical parkinsonian disorders, corticobasal syndrome and progressive supranuclear palsy. At post mortem, neuronal inclusions containing tau, TDP‐43 or infrequently FUS protein are seen in most cases. However, a poor correlation between clinical syndrome and underlying pathology means that it is difficult to diagnose the underlying molecular basis using clinical criteria. At this point, biomarkers for the underlying pathology come into play. This paper provides a brief update on fluid biomarkers for FTDs that may be useful to dissect the underlying molecular changes in patients presenting with signs of frontal and/or temporal lobe dysfunction. The hope is that such biomarkers, together with genetics and imaging, would be useful in clinical trials of novel drug candidates directed against specific pathologies and, in the long run, helpful in clinical practice to select the most appropriate treatment at the right dose for individual patients.